S1P transporter SPNS2 regulates proper postnatal retinal morphogenesis. Issue 7 (8th February 2018) - Fang, Chao; Bian, Ganlan; Ren, Pan; Xiang, Jie; Song, Jun; Yu, Caiyong; Zhang, Qian; Liu, Ling; Chen, Kun; Liu, Fangfang; Zhang, Kun; Wu, Chunfeng; et al.
Abstract : Spinster homolog 2 (SPNS2) is the membrane transporter of sphingosine‐1‐phosphate (S1P), and it participates in several physiologic processes by activating different S1P receptors (S1PRs). However, its functions in the nervous system remain largely unclear. We explored the important role of SPNS2 in the process of retinal morphogenesis using a spns2‐deficient rat model. In the absence of the functional SPNS2 transporter, we observed progressively aggravating laminar disorganization of the epithelium at the postnatal stage of retinal development. Disrupted cell polarity, delayed cell‐cycle exit of retinal progenitor cells, and insufficient migration of newborn neurons were proposed in this study as potential mechanisms accounting for this structural disorder. In addition, we analyzed the expression profiles of spns2 and s1prs, and proposed that SPNS2 regulated retinal morphogenesis by establishing the S1P level in the eye and activating S1PR3 signaling. These data indicate that SPNS2 is indispensable for normal retinal morphogenesis and provide new insights on the role of S1P in the developing retina using an established in vivo model.—Fang, C., Bian, G., Ren, P., Xiang, J., Song, J., Yu, C., Zhang, Q., Liu, L., Chen, K., Liu, F., Zhang, K., Wu, C., Sun, R., Hu, D., Ju, G., Wang, J. S1P transporter SPNS2 regulates proper postnatal retinal morphogenesis. FASEB J. 32, 3597–3613 (2018). www.fasebj.org